通分,再乘,得1/(a^2-b^2)
[(2/a-2b)+(1/a-b)]*[(a-2b)/(3a^2-ab-4b^2)]
1个回答
相关问题
-
{ab-[3a^2b-(4a^2b+1/2ab)]-4a^2b}+3a^2b}=
-
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)
-
-2ab(3a^2-2ab-4b^2) (2b-a)b-(2a-b)a
-
-3/4ab+2/3a^2b+ab-a^2b-1/2ab-5/3a^2b
-
1/4a^2b^2(3ab(a+b)-5a(ab-b^2))
-
1/2a^2b+(5a^2b-ab^2)-(-1/4a^2b+3a)-(3ab^2-6)
-
由(a+b)(a2-ab+b2)=a3-a2b+ab2+a2b-ab2+b=a3+b3,即(a+b)(a2-ab+b2)
-
已知A=2A^2+3ab-b^2,B=-1/2ab,C=3/2a^3b^3-1/4a^2b^4.求2A乘B^2-C
-
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
-
化简[(a-b)/(a+2b)]/[(a^2-b^2)/(a^2+4ab+b^2)]-(3a^2-4ab)/(a^2+a